Legal Review of Restrictions on the Import of Chinese Shipped Goods in E-Commerce Trading in Indonesia - Azizah, Mey Shinta Nur; Kusumo, Ayub Torry Satrio (International Journal of Sustainability in Research, 2024)
In accordance with Minister of Finance regulation No.141/PMK. April 2020, 2020 concerning monitoring the import and export of prohibited and/or restricted goods (bans and restrictions) in the field of online trading which occurs when the Company owner sends a shipment of imported goods to be purchased by consumers or directly from factories abroad. Online business people cannot just set up their business without knowing the regulations related to Lartas regarding prohibited goods and restrictions on imports into Indonesia. The role of legal awareness in society, which is a very objective legal goal, is to ensure legal certainty for society as an economic subject. The focus of this research is to find out the legal review of business actors regarding regulations related to Lartas, as well as knowing the regulations related to Lartas (prohibitions and restrictions) on the import of goods transported.